COMMUNITY EMPOWERMENT THROUGH THE SNACK VILLAGE PROGRAM IN KEDUNGSUMUR VILLAGE, KREMBUNG DISTRICT - Oktavia, Mirsa Pratama; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research investigates how the Snack Village Program in Kedungsumur Village, located in Krembung District, Sidoarjo, empowers the community. The local government launched this initiative to boost micro, small, and medium enterprises (MSMEs), particularly those producing traditional snacks, as a means to fortify the local economy. Method: Employing a qualitative descriptive approach, data were gathered through observation, interviews, and documentation involving essential contributors like village officials and MSME participants. Result: The results indicate that the Snack Village Program has played a crucial role in increasing the income of the community, especially benefiting housewives who had no independent sources of income before. The program has encouraged collaborative efforts, enhanced living standards, and focused on vulnerable segments by offering access to training, tools, and financial assistance. Capacity-building programs, including culinary workshops and marketing initiatives, have further improved skills and business competitiveness. Nonetheless, there are ongoing challenges, such as the rising costs of raw materials and reliance on traditional marketing methods, which hinder access to larger markets. Novelty: Despite these challenges, the initiative showcases a sustainable approach to community empowerment, integrating support from the government, involvement from the private sector, and active community engagement. In summary, the Snack Village Program emphasizes the significance of cooperative efforts in promoting inclusive economic development, preserving local culinary traditions, and enhancing rural self-reliance.